PEMETAAN KEBUTUHAN DAN PENGGUNAAN MEDIA PEMBELAJARAN 3D DI SEKOLAH DASAR KECAMATAN ILIR TIMUR II PALEMBANG - Wayan Arya Sugiarnawo (Jurnal PGSD Musi, 2019)
The background of this research is the limited use of media in teaching and learning in schools. This study is entitled "Mapping the Needs and Use of 3D Learning Media in Elementary Schools in Ilir Timur II District Palembang". The purpose of this study was to determine the needs and use of elementary school 3D media using the analysis method. This research is a qualitative study, a research that has a natural background, is descriptive, is more concerned with processes, tends to analyze data, and focuses on meaning. Data collection method by interview. From interviews conducted with five teachers in five elementary schools, it is known that 3D learning media is needed and they have never used it. From the results and discussion it can be concluded that all schools studied need 3D media and have not used 3D learning media.